Alonso Rodríguez Gamarra en el comercio de libros CON la América colonial (1607-1613) - Rueda Ramírez, Pedro (Revista General de Información y Documentación, 2009)
Alonso Rodríguez Gamarra was a book printer in Seville, that remained active between 1604 and 1622. He sent books in 1607 to Santo Domingo and in 1613 to Guatemala and Mexico. These three shipments were of 71, 295 and 186 respectively. Additionally, these shipments included 6000 printed sheet of broadside and chapbook in twelve ream of paper, that ,as a hole, was very well assorted. In two of the three registration sheets there was an unusual high level of detail of the books shipped, since there were notes of the title, the author and the imprint. This last detail has brought to us many surprises since it allows to make some clarifications on the production of Gamarra work shop. It is necessary to underline the reference to an unknown edition that appears declared by the printer himself as “Oraciones y exercicios de fr. Luis de Granada Sevilla por Alonso Rodríguez Gamarra 1612” (Sentences and Exercises by fr. Luis de Granada Seville by Alonso Rodríguez Gamarra).